Extending farmers’ reach beyond production: Development of Market linkages under Farmer FIRST Programme - Sharma, Pawan Kumar; Arora, R K; Kumar, Parveen; Singh, Rajbir (Indian Farming, 2021)
Indian agriculture has always been under stress due to inherent challenges such as lack of information, awareness and skills etc. on the latest agricultural technologies. However, under the present scenario, lot of efforts are required to move from production to market led extension, keeping in view the non-availability of remunerative price to the farmers. The Farmer FIRST Programme of Indian Council of Agricultural Research aims at moving beyond production and productivity to recognise the complex, diverse and risk prone realities of the farmers.